Exploratory Factor Analysis of Entrepreneurial Orientation among Small and Medium Scale Enterprises in Osun State, Nigeria - Ajayi(Fetuga)Omoshalewa Maryam (RUN JOURNAL OF MANAGEMENT, 2024)
Exploratory Factor Analysis (EFA) is required to show the correct items for usage in a research instrument. Thus, this study developed and validated an instrument of entrepreneurial orientation through exploratory factor analysis particularly in the context of Small and Medium Enterprises (SMEs) in Osun State Nigeria. The study examined innovativeness, pro-activeness, risk-taking, resource leveraging, autonomy and competitive aggressiveness as the core dimensions to measure entrepreneurial orientation. A questionnaire covering the six dimensions of entrepreneurial orientation was developed. This study adopted a multi stage sampling method, while quantitative data was collected from 312 out of the 340 selected Small and Medium scale Enterprises across Osun States, Nigeria. Based on the results of exploratory factor analysis, four factors were extracted and the factor represents; innovativeness, pro-activeness, resource leveraging, and competitive aggressiveness. Based on the findings, it was concluded that the four factors extracted play significant roles in the sustainable management of SMEs, hence, entrepreneurs should give utmost attention to them as entrepreneurial orientation is more relevant today to successfully run SMEs especially in the study area. Keywords: Entrepreneurial orientation, SMEs, Resource leveraging, Exploratory factor analysis, Competitive aggressiveness